Integrated Psychological Care is Needed, Welcomed and Effective in Ambulatory Inflammatory Bowel Disease Management: Evaluation of a New Initiative. (5th February 2019) - Lores, Taryn; Goess, Charlotte; Mikocka-Walus, Antonina; Collins, Kathryn L; Burke, Anne L J; Chur-Hansen, Anna; Delfabbro, Paul; Andrews, Jane M
Abstract: Background and Aims: Inflammatory bowel disease is associated with psychosocial issues which reduce quality of life and impair medical management. However, these issues are rarely addressed in routine care. A model of integrated psychological screening and intervention was trialled to measure prevalence, patient participation, and potential benefits to mental health and/or quality of life. Methods: During a 12-month period, 490 adult patients at an established hospital-based service were approached to complete screening instruments for anxiety, depression, general distress, quality of life and medication adherence. Disease-specific and demographic data were also collected. Patients who scored highly on screening questionnaires were offered psychological intervention (in-service or externally referred). Participants were reassessed after 12 months. Results: Psychological screening was well accepted with 68% ( N = 335) participating. Psychological care was 'needed', with 55% ( N = 183) scoring highly for anxiety, depression and/or general distress. Half of those 'in need' ( N = 91) accepted intervention. In those who accepted, levels of anxiety (mean at intake [ M1 ] = 12.11 vs mean at follow-up [ M2 ] = 9.59, p < 0.001), depression ( M1 = 8.38 vs M2 = 6.42, p < 0.001), general distress ( M1 = 17.99 vs M2 = 13.96, p < 0.001), mental health quality of life ( M1 = 54.64 vs M2 = 59.70, p < 0.001) and overall quality of life ( M1 = 57.60 vs M2 = 64.10, p < 0.001) each improved between intake and follow-up. Engagement in psychological intervention was six times greater for those treated in-service vs externally referred (χ 2 [1] = 13.06, p < 0.001, odds ratio = 6.47). Conclusions: Mental health issues are highly prevalent in people with inflammatory bowel disease. Patients are open to psychological screening and treatment. Psychological care can improve patient mental health and quality of life, and works best when integrated into routine management.